Lead the work : - Boudreau, John W. (John Wiley and Sons, 2015)
A detailed look at the evolution of employment and its far-reaching implications Lead the Work takes an incisive look at the evolving nature of work, and how it's affecting management and productivity at the organizational level. Where getting things done once meant assigning it to an employee, today's leaders are increasingly at risk if they fail to recognize that talent can float into and out of an organization. Long-term employment has given way to medium- or short-term employment, marking the first step in severing the bond that once fixed an individual inside an organization. Getting work done by means other than an employee was once considered a fringe event, but now leading organizations are accepting and taking advantage of the notion that talent has shown itself to be mutable. This book explores this phenomenon in detail and provides a new roadmap to help managers navigate this new environment. The workplace has undergone many changes over the years, but the emerging trend away from traditional employment represents a massive shift that has profound implications for the business model of every organization, large or small. This book describes how management is changing, and how managers must adapt to survive. Examine the dispersed organization and the changing nature of employment Learn how work is becoming impermanent and individualized Find new strategies for managing and leading Get up to speed on the decision science for the new era Workplaces evolve like biological beings; only the strong survive, and it's the competitive edge that ensures continued success. Lead the Work describes the new landscape, and shows you how to adapt and thrive.